Estudo de viabilidade hidráulica para a construção de uma mini central hidrelétrica - Sznicer, Geovane Polese (2015)
Unsurprisingly the large increase in the consumption of electricity, however the cost of electricity is too high, thus resulting in the need, where possible, to generate electricity for own consumption. There are several alternative power generation from photovoltaic, wind, and also, when the availability of rivers, small hydroelectric plants. This work is focused on the opportunity to build a hydroelectric generating plant in the country estate of Ary Prebianca Polese. As a contribution work shows the advantages and benefits provided to the independent producer of connecting a generating unit to a distribution system. Also touches on the subjects of hydrodynamics, Bernoulli's theorem, area calculation, arithmetic measures, generator, hydraulic turbines and electric generators. Shows surveying the river banks Jacutinga which is being carried out the study. It shows the behavior of the river Jacutinga for a period of six months. All information and concepts that are described in the work will be used to select the turbine pipe dimensioning and choice of the generator.